Letters from Iwo Jima - Eastwood, Clint, 1930-; Yamashita, Iris; Spielberg, Steven; Watanabe, Ken; Ninomiya, Kazunari; Ihara, Tsuyoshi; Kase, Ryo; Nakamura, Shidou; Dreamworks Picture; Warner Bros. Pictures (Burbank, California : Warner Bros. Pictures, 2006)
Untold story of the Japanese soldiers during World War II. With little defense other than sheer will and the volcanic rock of Iwo Jima itself, the unprecedented tactics of General Tadamichi Kuribayashi and his men transform what was predicted to be a swift defeat into nearly 40 days of heroic and resourceful combat. Their sacrifices, struggles, courage and compassion live on in the taut, gripping film Rolling Stone calls'unique and unforgettable.
Based on the book'Picture letters from Commander in Chief' by Tadamichi Kuribayashi, edited by Tsuyuko Yoshida and published by Shogakukan-Bunko.
Special features : Red Sun, Black Sand: The making of Letters from Iwo Jima and theatrical trailer.
Executive producer, Paul Haggis ; director of photography, Tom Stern ; co-producer, Tim Moore ; edited by Joel Cox.
Ken Watanabe, Kazunari Ninomiya, Tsuyoshi Ihara, Ryo Kase, Shidou Nakamura
Filmed on location on Iwo Jima, Japan and Southern California.
DVD format, Widescreen (2.40:1), Region 3, Dolby Digital.
Keywords: Kuribayashi, Tadamichi, -- 1890 or 1891-1945 -- Drama; Iwo Jima, Battle of, Japan, 1945 -- Drama; World War II -- Japan -- Drama; War films